Analysis of indicators of load during the game in activity of the second line attacker in water polo - Lozovina, V.; Pavicic, L.; Lozovina, M. (Collegium Antropologicum, 2002)
Water polo, as an activity, belongs in the category of polystructural complex move sports. The activities of a player`s in role of second line attacker is observed on the sample of competitive games in the First national league. The study is aimed to define a set of new measurement variables for the objective recording of amount, intensity and duration of player's activities, and its evaluation by means of factor validity criteria. On the sample of 87 players, 29 variables were applied. Competent, trained officials made measurements. Basic statistics of all measured variables is presented as referent values of various player activities. In the factor analysis, three factors are found to be significant, explaining 84.6% of source variability, which is a subset of multivariate normally, distributed variables. Factors are interpreted as: »quantity of actions«, »intensity of activity in the vertical body posture«, and »intensity and extensity of activity in horizontal body posture«. Of the last two, body posture is found to be specific in water polo, due to specifics of the game that is played in water. It is concluded that the proposed variables and measurement procedures are very well suited and objectively instrument for the purpose of measurement of the energetic aspect of kinesiological activity analysis.